KUALITAS E-SERVICE: DAMPAKNYA PADA KEPUASAN DAN LOYALITAS PELANGGAN (STUDI KASUS M-BANKING BANK BRI BANDAR LAMPUNG) - Farisi, Salman Al; Lestari, Winda Rika (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to determine the influence of E-Service Quality on customer satisfaction and its impact on Customer Loyalty of Bank BRI Mobile Banking (m-banking) users in Bandar Lampung. The type of research used is associative with a quantitative approach. The population in this research is BRI Bank customers who use the BRImo application. The type of sampling used in this research is a nonprobability sampling method using a purposive sampling technique. The data analysis method used is Smart PLS 4.0 analysis. The research results show that; 1) Customer Satisfaction is not positively influenced by Efficiency; 2) Customer Satisfaction is not positively influenced by Pulfilmment; 3) Customer Satisfaction is positively influenced by Privacy; 4) Customer Satisfaction is positively influenced by Responsiveness; 5) Customer Satisfaction is not positively influenced by Contact; 6) Customer Satisfaction is not positively influenced by Website Design; and 7) Customer satisfaction has a positive influence on customer loyalty. Keywords : E-Service Quality, Customer Loyalty, Customer Satisfaction